CLIMATE VARIABILITY AND IMPACT VULNERABILITY STATUS OF IRRIGATION WATER RESOURCES ON RICE AND TOMATO PRODUCTION DOWNSTREAM OF TIGA DAM, NIGERIA - Adegbehin, A. B.; Iguisi, E. O.; Yusuf, Y. O.; Dauda, C. K. (FUDMA JOURNAL OF SCIENCES, 2021)
The focus of this empirical study is to investigate the trends of some hydro metrological parameters and Impact Vulnerability Status (IVS) of irrigation water resources on rice and tomato production in the downstream of Tiga station. Investigation was conducted using data on rainfall, temperature, evaporation and reservoir water level for 30 years in Tiga station. The data collected was used to show the trend fluctuations of each parameter for the period of study. The rainfall data was also used to analyze the Normalized Rainfall Index (NRI) in order to know periods of surplus, deficit and optimal water availability as against the required water for rice and tomato production. The rainfall pattern and water level showed increasing trend while temperature and evaporation showed a general decrease in trend. The NRI used to investigate the IVS in Tiga station downstream revealed that rice and tomato were not vulnerable to drought and flooding for 18 years while every other years were vulnerable or slightly vulnerable. However, only year 1993 appears to be very wet and highly susceptible to flooding. Findings from focus group revealed that 80% of the farmers reported floods occurrences during rainy season and deficit of water between January and March of each year. In conclusion, the IVS of farmers to climate change revealed periods of deficit, optimal and excess water availability for rice and tomato production and their vulnerability status. It was recommended that the government should strengthen laws and policies relevant in addressing climate change
Keywords: Hydro metrological parameters, Irrigation water resources, Rice, Tomato production and Tiga dam.